Turbine Wind Placement with Staggered Layout as a Strategy to Maximize Annual Energy Production in Onshore Wind Farms - Hendrawati, Dwiana; Soeprijanto, Adi; Ashari, Mochamad (International Journal of Energy Economics and Policy, 2019)
The Wind Energy potential of Indonesia based on the General Plan of National Energy is 60,647.0 MW at wind speeds of 4 meters per second or more. Considerable potential and untapped optimally, is a challenge that gives direction to the development and policy of the wind energy sector in Indonesia. The policy covers a wide range of activities including study technology for utilization of large-scale wind energy source or called Wind Farms. To achieve these targets, the initial policy that can be applied is the utilization of wind energy and technology development of land-based wind farm for onshore wind farm. Land limitations on onshore directs this research in the attempt to increase AEP (Annual Energy Production) with a fixed land area. This is synonymous with minimizing the cost and is a WFO (Wind Farm Optimization) problem. The completion of WFO in this study was carried out by reconstructing the placement of wind turbines into a staggered layout. To test the performance improvement of the proposed design, by comparing the AEP of the proposed (staggered) layout and conventional (aligned) layout. The simulation shows that staggered layouts can reduce costs and increase AEP between 1.2-8.7%. Keywords: Wind Farms, Aligned and staggered layout, Cost, Annual Energy production JEL Classifications: C61, C63 DOI: https://doi.org/10.32479/ijeep.7437